Yevlampy Nadkin: The history and origin of the main comic strip character of the 1920s–1930s - A. A. Plekhanov (Шаги, 2025)
The article is devoted to the study of the genesis of Yevlampy Nadkin, one of the first widely known heroes of Soviet comics, and his embodiment in early Soviet media. Utilizing materials from newspapers and magazines such as Satyrikon, Novyi Satyrikon, Smekhach, Gudok, Begemot, and Leninskie iskry, as well as diaries and memoirs from the early 1900s to the 1930s, the study reveals that the artist Boris Antonovsky created Yevlampy Nadkin in 1925. This figure was based on Telegraphist Nadkin, a pre-revolutionary character originally conceived by Arkady Averchenko for the satirical journal Satyrikon. The editorial staff of Smekhach, many of whom were former employees of Satyrikon and Novyi Satyrikon, supported Antonovsky’s character, maintaining the biographical legend established by Averchenko. The similarity between the two figures may have been ignored in Soviet historiography due to Averchenko’s anti-Soviet views. The article traces Nadkin’s trajectory through the Soviet media during the 1920s and 1930s, illustrating how he migrated between publications amidst the centralization of Stalinist power. By 1933, Nadkin transformed into Yasha Nadkin in the children’s newspaper Leninskie iskry, where he continued to appear in comic strips, feuilletons, jokes, and caricatures until 1941. Even after Boris Antonovsky’s death in 1934, the character persisted in print. Additionally, the article highlights the theatrical and ballet adaptations of Yevlampy Nadkin for the first time.